Using stable water isotope composition (δ18O and δ2H) to track the interannual responses of Arctic and tropical Andean water bodies to rising air temperatures - Michelutti, Neal; Hargan, Kathryn; Kimpe, Linda; Smol, John; Blais, Jules (2022)
Lakes in the Arctic and tropical Andes are experiencing some of the largest temperature increases on the planet with coeval marked limnological changes, but little data exist on water balance parameters from these regions. Here, we present a unique data set of water stable isotope composition (δ18O and δ2H) from a suite of 49 waterbodies in the Canadian Arctic (Resolute Bay, Cornwallis Island, and Cape Herschel, Ellesmere Island) and the tropical Andes (Cajas National Park, Ecuador) spanning various years from 2009 to 2016. We show that an increase in air temperature over the study period resulted in evaporative enrichment of water isotopes in most Arctic sites highlighting the significance of evaporative losses to small Arctic ponds during the prolonged ice-free summers now experienced in this part of the world. Exceptions include some Arctic waterbodies that received abundant snowmelt and large, ice-covered lakes less prone to evaporation. Data from the Andean lakes indicated evaporative effects were minimal due to abundant precipitation. These data, in combination with limnological records and paleolimnological research from each region, provide a holistic view on how freshwater ecosystems are responding to recent warming in climatically sensitive Arctic and Andean environments.